2018
DOI: 10.1530/ec-18-0360
|View full text |Cite
|
Sign up to set email alerts
|

Virilising ovarian tumors: a single-center experience

Abstract: Literature on virilising ovarian tumors (VOTs) is limited to case reports and series reporting single pathological type. We have analyzed the clinical, hormonal, radiological, histological, management and outcome data of VOT. This retrospective study was conducted at a tertiary health care center from Western India. Consecutive patients with VOT presenting to our endocrine center between 2002 and 2017 were included. Our study included 13 patients of VOT. Out of 13 patients, two were postmenopausal. All patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(18 reference statements)
1
2
0
1
Order By: Relevance
“…Our study is the first to demonstrate that VOTs are significantly smaller in postmenopausal women than in premenopausal women. In accordance with a previous report [ 6 ], the most common VOT was Sertoli-Leydig cell tumors. The present study revealed that the most common histotypes differed between premenopausal and postmenopausal patients, with Sertoli-Leydig cell tumors in premenopausal patients and Leydig cell tumors in postmenopausal patients.…”
Section: Discussionsupporting
confidence: 92%
“…Our study is the first to demonstrate that VOTs are significantly smaller in postmenopausal women than in premenopausal women. In accordance with a previous report [ 6 ], the most common VOT was Sertoli-Leydig cell tumors. The present study revealed that the most common histotypes differed between premenopausal and postmenopausal patients, with Sertoli-Leydig cell tumors in premenopausal patients and Leydig cell tumors in postmenopausal patients.…”
Section: Discussionsupporting
confidence: 92%
“…Study strength. Over the past decades, a relatively small number of clinical cases of LCTs and case series have been published [ 32 , 33 , 34 , 35 , 36 ]. Therefore, the demonstration of our observations is valuable and allows for replenishing the database available for pooled analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Representan el 1-2% de la amenorrea con hirsutismo severo. Los tumores virilizantes ováricos pueden ser de Sertoli-Leydig, de la teca granulosa, de células lipídicas, de células hiliares, de restos adrenales, disgerminomas y gonadoblastomas (37,38). Por su parte, los suprarrenales son adenomas y carcinomas (39).…”
Section: Tumores Productores De Andrógenosunclassified